Effects of Black Soldier Fly Larva Meal Oil in the Diet on Production Performance, Feed Cost, and Egg Quality of Laying Hens - Nonok Supartini; Puspita Sovie Juniar; Nisa Bejawati; Hariadi Darmawan; Sumarno (ANIMAL PRODUCTION, 2026)
This study assessed the production performance, economics, and egg quality of laying hens fed with 0%, 4%, 8%, and 12% Black Soldier Fly larval meal oil or maggot meal oil (MMO). Forty-eight Hy-Line Brown hens (50–60 weeks old) were allocated to four treatments (three replicates of four hens) in a completely randomized design over 30 days. Feed intake, hen-day production (HDP), feed conversion ratio (FCR), and income over feed cost (IOFC) were measured, alongside external and internal egg quality. MMO inclusion up to 12% did not significantly alter feed intake, HDP, or FCR (P > 0.05), though 8% MMO yielded the highest intake (120.1 g/head/day) and HDP (93.8%), and 12% MMO achieved the best FCR (1.13). IOFC rose at an MMO level, peaking at Rp 45,340 for 12% MMO. All egg quality traits, including shape index, weight, shell strength, air-cell depth, albumen and yolk indices, and Haugh Units, remained within Grade A standards. These results indicate that MMO can be used up to 12% of the diet without compromising production or egg quality while improving economic returns, and this study recommends an inclusion of 8% MMO to optimize production efficiency and profitability.